Present at the Past. - Fried, Ellen (Prologue)
Presents information on several National Archives' Public Vaults exhibits. Documents included in the initial display of "Reports From the Front," which showcased first-person battle accounts by servicemen and women in the field; Records that visitors can explore in the interactive unit "Investigations"; Features of the software used in the interactive unit "Top Secret," that allows the visitor to snoop through the secrets of U.S. history.